Characterization of Polysulfone Membrane with Variation of Ethanol Concentrations in Coagulation Bath for Ultrafiltration Membrane - Indarti, Dwi; Henry Adi Syahputra Sidabutar; Handayani, Wuryanti; Piluharto, Bambang (Indonesian Chimica Letters, 2023)
The aim of this research is to study influence of ethanol concentrations in coagulation bath to charecteristic of physical properties and polysulfone membrane performance. Ethanol concentrations that used is 0; 40; 50; 60 ; 70; 80; 90 %. Process of making for polysulfone ultrafiltration membrane is prepared with phase inversion technique. Polysulfone membrane is made from polysulfone solved in N,N- dimetilacetamida (DMAc) and additive poly(ethylene glikol) (PEG) 600 in proportion 18 %: 77 %: 5 %. The result showed that increasing ethanol concentrations causes the increasing of density and increase concentrations from 0 - 50 % causes increasing swelling degree, but decreasing swelling degree from concentrations 60 - 90 %. However influence of ethanol concentration in coagulation bath to membrane performance is increasing of water flux, permeability coefficient, and rejection coefficient to dextran. It based on of result that polysulfone membrane with ethanol concentrations 80 dan 90 % included membrane classification ultrafiltration by rejection coefficient value above 90 %.